A bibliometria e a pesquisa interdisciplinar nas ciências ambientais - Romanelli, João Paulo (Universidade Federal de São Carlos, 2019)
In recent years, research results on Environmental Sciences have grown in complexity and proportion, and this has required from the scientists the capacity to synthesize information from different sources to support holistic analyzes and generate new knowledge. Bibliometric analysis appears in this context as an analytical tool with high potential to support the systematic synthesis of information and the analysis of the outptus of science. In this thesis, we seek to evaluate how bibliometric tools and methods can contribute to the generation of new knowledge and analysis of science, presenting five articles developed from topics of Environmental Sciences and its subfields. Specifically, in Chapter 1 we explored different forms of network analysis and introduced an unprecedented methodology of keyword analysis to detect research gaps in the area of Restoration Ecology. This same methodology was used in Chapter 2, where we investigated the research on the enzymes immobilization. We introduced spatial analysis resources to complement the discussion of network analysis and analyzed the dynamics of bibliometric indicators in different periods (27, 10 and 5 years). In Chapter 3, we emphasized country-stratified research, and through the co-occurrence criterion of keywords we present the main research topics on electronic waste management. In Chapter 4, two distinct focuses of study were presented: an applied research related to the restoration of ecosystems; and a practical and theoretical approach related to qualitative chemistry, intermediated by the Laser-Induced Breakdown Spectroscopy (LIBS) technique and by bibliometrics, respectively. In this chapter, we present a new perspective on the use of bibliometric indicators to support research. Finally, in chapter 5 we had the opportunity to work with the smallest database among the studies of this thesis, which generated several insights on the performance of the bibliometric indicators in "narrow" bases; which was analyzed under Ostrom's precepts on common forest management. From the perspective of bibliometrics scholars related to the non-LIS community (Library and Informations Science), we had as general objective: to discuss and synthesize information on the use of bibliometric indicators in the research of Environmental Science topics. The results indicate, for a great diversity of subjects, that the application of bibliometric tools is an effective way of revealing the current state of the research and its directions, which can favor the development of new studies and scientific production in Environmental Sciences.
Bibliometrics and interdisciplinary research on environmental sciences
Keywords: Pesquisa interdisciplinar; Interdisciplinaridade; Análise bibliométrica; Bibliometria; Ciências ambientais; Interdisciplinary research; Interdisciplinarity; Bibliometric analysis; Bibliometrics; Environmental sciences; CIENCIAS BIOLOGICAS